Outpatients’ satisfaction with healthcare services received at a district hospital in Botswana - Khuwa, Zibo K.; Matlala, Sogo F.; Ntuli, Thembelihle S. (My University, 2022)
SUMMARY Objectives: To investigate patient satisfaction regarding healthcare services at a district hospital. The research ques-tion was: what is the level of patient satisfaction regarding service delivery? Design: An observational cross-sectional descriptive study conducted in September 2019. Settings: A district hospital in Botswana serving a population of 90 000. Outpatients from the Eye clinic, Casualty and Outpatient Department, Sexual Reproductive Health clinic and Infectious Diseases Control Centre were selected for the study Participants: 240 stable outpatients over 17 years selected through consecutive sampling participated voluntarily after giving informed consent. Main outcome measures: The level of satisfaction was measured using 19 questions on five-point Likert scales rang-ing from strongly disagree 1, disagree 2, unsure 3, agree 4 to strongly agree 5. A binary outcome was created into satisfied and unsatisfied using the mean score as the cut-off point. Age, gender, employment, education and depart-ments were independent variables. Results: 65% (95% CI: 58-71%) were satisfied but unsatisfied with: doctor’s politeness (66.9%; 95% CI: 60-73%), explaining (67.8%; 95% CI: 61-73%), privacy (65.6%; 95% CI: 59-72%), skills (67.4%; 95% CI: 61-73%), confidence (67.4% 95% CI: 61-73%), compassion (66.5%; 95% CI: 60-72%) and waiting time (49.2%; 95% CI: 42-57%). De-partment visited predicted satisfaction (p=0.002); those from the Eye clinic and Sexual Reproductive Health clinic were satisfied compared to others. Conclusion: Satisfaction was generally high but lower regarding specified services and departments visited. There is a need for targeted interventions. Studies are needed to explore reasons for lower satisfaction in Casualty, Outpatient Department and Infectious Diseases Control Centre.
Journal article published in Ghana Med J 2022; 56(3): 215-220
Keywords: District hospital; Healthcare professionals; Patient satisfaction; Quality healthcare services; Patient satisfaction; Medical personnel; Medical care -- Botswana; Hospital patients -- Care; Hospital patients -- Services for